How to reduce synthetic oxytocin administration and stimulate the production of endogenous oxytocin in childbirth - Antonio Ragusa (Hygeia Press di Corridori Marinella, 2015)
The purpose of this review is to examine synthetic and natural oxytocin use in pregnancy and post-partum. We distinguished synthetic oxytocin (Syntocinon®) use in labor as a uterine contraction stimulant in two parts: the first is for induction or augmentation of labor; the second for prevention of post-partum hemorrhage (PPH). Oxytocin, key hormone in the process of childbirth and lactation, is a strong smooth muscle stimulant. For this reason it is widely used to induce/augment labor and to prevent and cure PPH. However, Syntocinon® can penetrate the placenta and reach fetal circulation, thus causing various systemic effects on mother and fetus. Oxytocin plays an important role as a neurotransmitter in the central nervous system, affecting numerous neuro-behavioral functions and it is involved in many types of parental behavior in humans and animals. It is, in fact, involved in a wide variety of physiological and pathological functions such as sexual activity, penile erection, ejaculation, pregnancy, uterus contractions, milk ejection, maternal behavior, social bonding, and stress. Oxytocin has a decisive role in the process of "bonding" between mother and child and in that of social affiliation. We therefore explored the opportunity to reduce the use of Syntocinon® in labor ward as a precautionary measure. Finally, we place the emphasis on some techniques that will probably increase the production of endogenous oxytocin.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)